Peran Etika dan Estetika Filsafat Dalam Layanan Bimbingan Konseling - Chandra, Mutiara Putri; Karneli, Yeni; Handayani, Puji Gusri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article discusses in depth the role of ethics and aesthetics of philosophy in the science of guidance and counseling, how the two complement each other, and their practical implications in improving the professionalism and effectiveness of guidance and counseling services. This article was compiled using a literature review method. Previous scientific works related to the literature review are the main sources of this research. Data collection methods include books, journal articles, internet articles, and other writings related to the subject (Ridwan et al., 2021). This study analyzes how the role of ethics and aesthetics is applied in guidance and counseling services. This study does not involve direct sampling or subjects, unlike the quantitative approach. Researchers focus on analyzing literature relevant to the topic as a basis for drawing conclusions. The results of the study show that in guidance and counseling, ethics and aesthetics of philosophy have a very important and complementary role in guidance and counseling services. Ethics function as a moral foundation that directs the professional behavior of counselors to always uphold the rights and dignity of clients, maintain confidentiality, and act fairly and responsibly. Meanwhile, aesthetics play a role in creating a comfortable and conducive counseling atmosphere through the physical environment, communication style, and the appearance and attitude of the counselor, so that clients feel valued, accepted, and motivated to open up.